Pengembangan Canting Batik Cap Modular untuk Produksi Batik Berkelanjutan - Andri Nur Cahyo; Mursidah; Intan Pratiwi (JURNAL RUPA, 2025)
The national batik industry faces challenges in increasing production efficiency without sacrificing traditional values and environmental sustainability. One of the current challenges lies in the limited flexibility of conventional canting cap tools in accommodating diverse motif variations, which may affect production efficiency and material utilization. This research aims to develop a canting cap based on a modular design that allows batik artisans to arrange, replace, and combine stamp elements as needed. The research method uses a Research and Development (R&D) approach with a design thinking and participatory design model. The process includes problem identification, prototype design, testing, and evaluation with batik artisans. The research results produced a prototype of a modular canting cap made from recycled duplex paper with three mechanism configurations: modular Mechanical interlocking, modular light magnetic locking, and modular strong magnetic locking. The strong magnetic locking configuration proved to be the most ideal because it is stable, precise, and supports the principle of zero waste. This innovation contributes to production efficiency, waste reduction, and supports the transformation of batik into a sustainable creative industry.